Clinical Characteristics, Management and In-Hospital Outcomes of Children with Polymerase Chain Reaction (PCR)-Confirmed Pertussis at a Provincial Referral Hospital in Vietnam - Pham Thi Thanh Huong (Journal of Pediatric Advance Research, 2026)
Background: Pertussis remains an important cause of hospitalization in young infants, particularly before completion of primary immunization. Methods: We conducted a single-center observational study of 36 consecutive children hospitalized with real-time polymerase chain reaction-confirmed Bordetella pertussis infection from 1 April 2024 through 31 March 2025. Demographic, vaccination, clinical, laboratory, radiographic, treatment and in-hospital outcome data were summarized. Because of the small sample and sparse outcome counts, associations with transfer to a higher-level hospital were assessed using two-sided Fisher exact tests and interpreted as exploratory. Results: The mean age was 13.73 months, 21 children (58.3%) were male and 13 (36.1%) were aged